More Letters for the Roberts Collection - Adams, John Coldwell (Studies in Canadian Literature, 1991)
The seven cards and letters which Charles G.D. Roberts wrote to Kathleen Strathearn from the winter of 1926-27 to the summer of 1928 document the writer's infatuation with the much-younger pianist. The seven reproduced letters reveal Roberts's passionate pursuit of Kathleen and her less-than-enthusiastic response to the suit of the impoverished and married writer. Kathleen was replaced in Roberts's affections by Joan Williams, whom he eventually married; Kathleen married twice and had a successful career as a pianist/ hostess in Asia.